The Combination of Carbon Source and the Addition of Phenylacetic Acid (PAA) to Growth Medium Penicillium chrysogenum to Enhance of Penicillin (Pen G) Production - Martha Sari; Dirayanti Dirayanti; Eris Septiana; Bustanussalam Bustanussalam; Apon Zaenal Mustopa (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2020)
The nutrition factor governs the growth and production of Penicillin G (Pen G) by Penicillium chrysogenum in a broth medium. Proper nutrition can improve Pen G antibiotic production. In this research, the optimal condition for Pen G production from P. chrysogenum in a standard culture medium and various carbon sources medium (glucose, lactose, maltose, and sucrose) were done for ten days. Phenylacetic Acid (PAA) precursor at 0.0 – 0.6 gL-1 (increment 0.1) was used to improve Pen G production. The Pen G was detected by HPLC, compared with the standard (Penicillin G Sodium Salt). The results showed that the PDB standard medium and lactose medium (150 rpm, at 30°C) produced 0.425 gL-1 and 0.107 gL-1 Pen G. Addition of 0.6 gL-1 PAA improved the Pen G production up to 0.045 gL-1 in the PDB medium, become the final concentration of 0.470 gL-1 and 2.460 gL-1 in the lactose medium, become the final concentration of 2.565 gL-1. The antibiotic’s activity against the pathogenic bacteria, i.e., B. subtilis, S. aureus, and S. typhi employing the disk diffusion method, has been done. The TLC method’s detection of the potential Pen G spots was conducted with ethyl acetate: distilled water: acetic acid (60:20:20) as the mobile phase. The Pen G extracts could inhibit the growth of all tested bacteria in Rf 0.65. This study informs the proper combination of carbon source and precursor effects and increases the bioproduction of Pen G from P. chrysogenum.